Therapeutic Management of Chronic Renal Failure in a Dog - Behera, S. K.; Ghorai, S.; Haji, M. M.; Ravindran, R.; Shah, N.; Das, Gunjan (International Journal of Livestock Research, 2018)
A case of chronic renal failure was diagnosed in an eight year old Labrador dog on the basis of history, clinical signs, physical examination, hematology, plasma biochemistry, followed by confirmation with the help of ultrasonography and urinalysis. Urinalysis on the day of presentation revealed turbid straw colored urine, decreased specific gravity, trace amount of non-haemolysed blood, alkaline pH, marked proteinuria and pyuria with high inflammatory cells and epithelial cast. Basing on the plasma creatinine value, the case was diagnosed as terminal stage 4 chronic renal failure. The patient was treated with fluid therapy, antibiotic, antacid, antiemetic, calcium supplement, multivitamin, and erythropoietin. Though the prognosis in case of end stage chronic renal failure is guarded, nevertheless, it took 30 days to bring back the animal from stage 4 to stage 2 with clinical signs of improvement and it was followed up to 5 months without any further complication.